Purse-string closure versus conventional primary closure of wound following stoma reversal: Meta-analysis of randomized controlled trials. (April 2018) - Rondelli, Fabio; Franco, Laura; Balzarotti Canger, Ruben Carlo; Ceccarelli, Graziano; Becattini, Cecilia; Bugiantella, Walter
Abstract: Purpose: Surgical site infection (SSI) is one of the most frequent complications after stoma closure and the optimal skin closure technique is still not clear. The goal of this review was to compare outcomes with purse-string closure technique (PSC) versus conventional closure technique (CCT) for skin closure after stoma reversal. Methods: We performed a systematic review and meta-analysis of available randomized controlled trials (RCTs) to compare SSI rate within 30 days, operative time, hospital stay, incisional hernia and intestinal obstruction rates between PSC and CCT. Results: The pooled analysis of 5 studies showed a statically significant lower rate of SSI in favor of PSC compared to CCT (OR -0.24; 95% CI -0.32, - 0.15; p < 0.00001). No statistically significant differences were observed in the operative time (OR -0.05; 95% CI -3.95, 3.84; p = 0.98) and in the length of hospital stay (OR -0.20; 95% CI -0.76, 0.36; p = 0.48), between the two techniques. Additionally, two out of the five studies provided data on incisional hernia and intestinal obstruction and the pooled analysis revealed no statistically significant differences between PSC and CCT techniques: incisional hernia (OR 0.81, 95% CI 0.27–2.47; p = 0.71) and intestinal obstruction (OR 1.07, 95% CI 0.41–2.84; p = 0.88). Conclusions: The analysis of 5 RCTs showed that SSI rate is statistically significant lower when PSC is performed, compared to CCT. Whereas, no significant differences were found between the two techniques with regards to operative time, length of hospital stay, incisional hernia and intestinal obstruction rates. Highlights: Surgical site infection (SSI) is one of the most frequent complications after stoma closure. We compared outcomes with purse-string closure technique (PSC) versus conventional closure technique (CCT) for skin closure after stoma reversal. Five RCTs were included in the meta-analysis resulting in 385 patients. The meta-analysis showed a statically significant lower rate of SSI in favor of PSC compared to CCT. PSC should be adopted as skin closure technique after stoma reversal.